The influence of confining stress and chemical alteration on conductive pathways within wellbore cement - Huerta, Nicolas J.; Bryant, Steven L.; Strazisar, Brian R.; Kutchko, Barbara G.; Conrad, Lauren C. (Energy procedia, 2009)
Wells remain inadequately studied with respect to the probability and rate of leakage in geologic CO2 sequestration. Efforts to model reaction-induced leakage along wells have been limited due to poorly understood reaction between cement and sequestered CO2 fluids. Recent work on class H cement under reservoir conditions has shown a slow reaction rate, even considering the timescale of interest for CO2 sequestration (Kutchko et al. [1]). This observation is consistent -with field scale observations at a CO2 enhanced oil recovery operation (Carey et al. [2]). These results suggest that loss of well integrity from degradation of intact cement is not a significant leakage risk. However, cement failure via micro annulus debonding and micro fracturing of the cement is a relatively common occurrence in the petroleum industry. If the CO2 plume were to encounter these conductive pathways, leakage out of the storage volume could occur. If CO2-saturated brine were to move into these conduits, reactive alteration of cement would be focused on the conduit walls. Further complicating the scenario is the fact that wells are subject to geomechanical stresses. To properly assess the leakage risk of wells around a CO2 sequestration project, we need to determine whether degradation of cement along a conductive pathway will increase or decrease its conductivity. Here we report a set of simple experiments studying this coupled relationship. The experiments measure flow through a fracture in a core, from which we infer its effective aperture as a function of confining pressure. Class H neat cement was cast in cylindrical cores and fractured using the Brazilian method to create a more realistic pathway geometry. Core halves were reassembled with a small offset to prevent mating, then sealed to ensure flow only through the fracture. We observe a systematic variation in effective aperture, and hence in conductivity, with confining stress. The variation is consistent with behavior reported in the literature. The disassembled fracture faces were then degraded with hydrochloric acid to simulate exposure to CO2-saturated brine along this conductive pathway. A reassembled, lightly reacted fracture behaves similarly to the unreacted fracture. A heavily reacted fracture closes much faster as confining stress increases. Thus the coupling between reaction and geomechanics in the field will strongly affect the leakage rate; indeed, it raises the possibility that leaks could be self-sealing.